Magnetic resonance-guided stereotactic body radiotherapy (MRIgSBRT) for nodal disease in oligometastatic setting: a single-institution study - Giuditta Chiloiro; Giulia Panza; Angela Romano; Rosa Autorino; Ciro Mazzarella; Gabriele Turco; Marco Valerio Antonelli; Matteo Nardini; Simone Raggio; Lorenzo Placidi; Maria Antonietta Gambacorta; Luca Boldrini (Clinical & Experimental Metastasis, 2026)

Short-term feed withdrawal does not alter morpho-physiological stress response in adult zebrafish - Elisa Fonsatti; Martina Bortoletti; Daniela Giaquinto; Maria Raggio; Elena Negrato; Paolo de Girolamo; Giuseppe Radaelli; Livia D'Angelo; Daniela Bertotto (Research in Veterinary Science, 2025)

Modelling orexinergic system in ageing in the African turquoise killifish - Maria Raggio; Ivan Conte; Paolo de Girolamo; Livia D’Angelo (Biogerontology, 2025)
The orexinergic system is anatomically and functionally conserved in almost all vertebrates, and the role in healthy ageing and age-associated diseases has been studied in mammals. Here, we review the main findings on the age-related regulation of orexinergic system in mammals, including human patients and highlights how the fish Nothobranchius furzeri serves as an exceptional model to spearhead research and unravel the intricate mechanisms underlying orexinergic regulation during ageing. The ageing brain of this teleost is characterized by the presence of neurodegenerative processes similar to those associated with human pathologies rather than those of healthy ageing. We present an in-depth summary and discussion on the groundbreaking advances in understanding the neuroanatomical organization of the orexinergic system, its pivotal role in mammalian and fish models, and its profound involvement in healthy ageing and age-associated diseases.

Behavioral alterations and gills damage in Mytilus galloprovincialis exposed to an environmental concentration of delorazepam - Chiara Fogliano; Rosa Carotenuto; Raffaele Panzuto; Valentina Spennato; Salvatore De Bonis; Palma Simoniello; Anja Raggio; Bice Avallone; Claudio Agnisola; Chiara Maria Motta (Environmental Toxicology and Pharmacology, 2023)